Legal Certainty in the Determinant Application of Customary Law in Indonesian National Criminal Law - Immanuel Joyson Benaya Manurung; Andi Hakim Lubis (PT ARFA DIGITAL TECHNOLOGY, 2025)
Customary criminal law is an integral part of Indonesia's legal heritage that has long been studied, from the thoughts of Snouck Hurgronje to Van Vollenhoven. Its recognition in Article 18B paragraph (2) of the 1945 Constitution and its incorporation into the new Indonesian Penal Code (KUHP) mark significant steps toward developing a legal system that aligns more closely with Indonesia's social conditions while reducing dependence on colonial laws. However, this recognition also brings consequences, particularly concerning the formalization, requirements, and limitations imposed on customary law. This raises the question of whether customary criminal law will introduce a new dimension to the national legal system or create dualism in its application. This article will examine legal certainty following the implementation of customary criminal law in the Criminal Code and its impact on law enforcement processes in Indonesia.